A critical review of the performance evaluation and optimization of grid interactions between zero-energy buildings and power grids. (November 2022) - Zhang, Wenjie; Yan, Chengchu; Xu, Yizhe; Fang, Junjian; Pan, Yan
Highlights: A critical review of the grid interaction between ZEBs and power grids. Independence, stability and friendliness indicators are classified. The factors affecting the accuracy of evaluation indicators are analyzed. Optimizations in terms of building, grid and interactive platform are presented. Abstract: Grid-friendly interaction is the basis for a zero-energy building to achieve its annual energy balance goals through participation in renewable power sharing with grids and is therefore the premise for the large-scale application of zero-energy buildings. How to effectively evaluate and optimize the interaction performance is the key to promoting friendly interaction between zero-energy buildings and power grids. This paper provides a comprehensive overview of grid interactions, including grid-interaction (GI) indicators for performance evaluation, the application of such indicators and optimization measures for achieving grid-friendly interactions. First, the existing GI indicators are classified into three typical types, namely, independence indicators, stability indicators and friendliness indicators, from the perspective of how to understand and address the GIs. The typical applications of such indicators at various time scales and from different data sources are summarized. Second, the optimization measures for enhancing the interaction performance between zero-energy buildings and power grids are reviewed based on the efforts from the building side and grid side and the development of interactive platforms and facilities. Finally, the limitations of current research and the direction of future work on the interaction between zero-energy buildings and power grids are summarized.